Deficit Irrigation Strategies for Subsurface Drip-Irrigated Alfalfa - F. R. Lamm; R. Reyes-Esteves; K. R. Harmoney (Kansas Agricultural Experiment Station Research Reports, 2022)
This subsurface drip-irrigated study was conducted from 2020 to 2021 at the Kansas State University Northwest Research-Extension Center near Colby, KS, to evaluate five deficit irrigation strategies for alfalfa. All strategies were irrigated similarly (100% of Evapotranspiration (ET) minus Rain) through the first seasonal cutting. Following the first cutting, treatments were 1) Irrigate to replace 85% ET minus Rain; 2) Irrigate to replace 50% ET minus Rain between Cutting 2 and 3, then 85% ET-Rain; 3) Irrigate to replace 50% ET minus Rain between Cutting 2 and 4, then 85% ET-Rain; 4) Irrigate to replace 70% ET minus Rain between Cutting 2 and 4, then 85% ET-Rain; and 5) Irrigate to replace 25% ET minus Rain between Cutting 2 and 3, then 85% ET-Rain. Average alfalfa forage dry matter yields varied less than 5% across treatments (9.52 vs. 9.94 ton/a) while irrigation requirements varied 20% (17.50 vs. 22.03 inches). Overall, the best treatments appeared to be treatments 2 and 3, obtaining both good yields and greater water productivity.
Keywords: irrigation; subsurface drip irrigation; alfalfa; evapotranspiration